Preparation and characterization of primary magnesium mixtures for the ab initio calibration of absolute magnesium isotope ratio measurements. Issue 1 (2nd September 2015) - Brandt, Björn; Vogl, Jochen; Noordmann, Janine; Kaltenbach, Angela; Rienitz, Olaf
Abstract : Isotope mixtures for the ab initio -calibration of Mg isotope ratio measurements were prepared with unrivalled relative expanded uncertainties as low as 0.005%. Abstract : We report an appropriate preparation of binary isotope calibration mixtures of the three stable isotopes of magnesium to be used in the ab initio calibration of multicollector mass spectrometers (ICPMS and TIMS). For each of the three possible combinations of binary mixtures (" 24 Mg" + " 25 Mg", " 24 Mg" + " 26 Mg", and " 25 Mg" + " 26 Mg"), three individual setups have been prepared under gravimetric control, each of them with an isotope ratio close to unity, and a total magnesium mass fraction close to 20 mg kg −1 . The preparation was designed to occur via an intermediate dilution of a parent solution of a highly purified specimen of the isotopically enriched magnesium materials. For the application as calibration mixtures, a complete uncertainty budget was set up, and is presented and discussed in detail, including the aspects that went into the design of the dilution and mixing approach to minimize uncertainty. The principle parameters for the purpose of the later calibration of the mass spectrometers are the absolute masses of isotopically enriched magnesium materials in the primary calibration mixtures. For the first time relative expanded uncertainties U ( k = 2) for these masses of ≤0.005% could be achieved for all mixtures.